Progressive myoclonic epilepsy as an adult-onset manifestation of Leigh syndrome due to m.14487T>C. Issue 1 (17th December 2009) - Dermaut, B; Seneca, S; Dom, L; Smets, K; Ceulemans, L; Smet, J; De Paepe, B; Tousseyn, S; Weckhuysen, S; Gewillig, M; Pals, P; Parizel, P; et al.
Abstract : Background: m.14487T>C, a missense mutation (p.M63V) affecting the ND6 subunit of complex I of the mitochondrial respiratory chain, has been reported in isolated childhood cases with Leigh syndrome (LS) and progressive dystonia. Adult-onset phenotypes have not been reported. Objectives: To determine the clinical–neurological spectrum and associated mutation loads in an extended m.14487T>C family. Methods: A genotype–phenotype correlation study of a Belgian five-generation family with 12 affected family members segregating m.14487T>C was carried out. Clinical and mutation load data were available for nine family members. Biochemical analysis of the respiratory chain was performed in three muscle biopsies. Results: Heteroplasmic m.14487T>C levels (36–52% in leucocytes, 97–99% in muscle) were found in patients with progressive myoclonic epilepsy (PME) and dystonia or progressive hypokinetic-rigid syndrome. Patients with infantile LS were homoplasmic (99–100% in leucocytes, 100% in muscle). We found lower mutation loads (between 8 and 35% in blood) in adult patients with clinical features including migraine with aura, Leber hereditary optic neuropathy, sensorineural hearing loss and diabetes mellitus type 2. Despite homoplasmic mutation loads, complex I catalytic activity was only moderately decreased in muscle tissue. Interpretation: m.14487T>C resulted in a broad spectrum of phenotypes in our family. Depending on the mutation load, it caused severe encephalopathies ranging from infantile LS to adult-onset PME with dystonia. This is the first report of PME as an important neurological manifestation of an isolated mitochondrial complex I defect.